Ethnopharmacological Inspections of Organic Extract of Oroxylum indicum in Rat Models: A Promising Natural Gift. (3rd April 2019) - Begum, Mst. Marium; Islam, Azharul; Begum, Rayhana; Uddin, Md. Sahab; Rahman, Md. Sohanur; Alam, Sumiya; Akter, Wahida; Das, Munny; Rahman, Md. Sohanur; Imon, A. H. M. Rahmatullah
Abstract : The stem bark of Oroxylum indicum ( O. indicum ) was aimed at testing for anti-inflammatory, antiulcerative, antihyperglycemic, and antidyslipidemic activities. Liver enzyme concentration (SGPT, SGOT) had also been assessed. After being extracted in organic solvent, 3 distinct doses, 100, 200, and 400 mg/kg b.w. (p.o.), were used. For edema formation 0.1 ml carrageenan at a dose of 1% w/v was injected into paw of left hind. It showed a fall of edemas 37.50%, 48.34%, and 55.83% while used doses were 100, 200, and 400 mg/kg b.w. (p.o.) individually. The EtOH extract of O. indicum (50%) and its fractions PET, CLF, EtOAc, and nBUT were studied against ethanol-induced gastric mucosal damage. Only PET and n-BuOH exhibited the highest percentage of protection and were 96% and 99%, respectively, persuaded by ethanol. In OGTT glibenclamide revealed reduction of glucose level to 7.55 ± 0.22 mmol/L from 10.57 ± 0.32 mmol/L after 30 minutes. Antihyperglycemic activities were assessed for 8- and 12-week duration in diabetic rats. Glibenclamide reduced glucose level from 33.50±0.31 to 7.90±0.19 mmol/L in 12 weeks. In 12 and 8 weeks, combination therapy lowered blood glucose level to a normal extent by 79% and 61% individually. In antidyslipidemic activities after 12-week treatment, it revealed simvastatin; MEOI (400 mg/kg b.w.) and combination of both reduced TC level by 44%, 28%, and 48% consequently followed by TG and LDL. In 8-week treatment, HDL levels were increased by 34%, 13%, and 36%, and in 12 weeks increased by 36%, 8%, and 38% consequently. Liver enzyme concentration after 12 weeks of treatment with glibenclamide, 400 mg/kg b.w. (p.o.) of MEOI and combination of both, exhibited the fact that concentration of SGPT showed downturn by 43.23%, 8.01%, and 54.86% and SGOT by 42.40%, 5.31%, and 44.85%. This study remarked that O. indicum has anti-inflammatory, antiulcer, antidiabetic, and antidyslipidemic potentials but has no ameliorative effect on liver enzyme.